High Voltage Inductor Design for Synthetic Testing of a Supercritical CO2 Circuit Breaker - Hossain, Mohd. Sadeed Al; Li, Tianchen; Jin, Jhiyang; Graber, Lukas; Park, Chanyeop (Electrical Insulation Conference and Electrical Manufacturing Expo, 2023)
Global warming has been a burning issue since the 1980s, and SF 6 has been one of the most potent global-warming gases used by the power industry. SF 6 is used in high-voltage circuit breakers. They are prone to leakage into the atmosphere, creating adverse effects on the environment. Replacing SF 6 with supercritical CO 2 as the arc quenching medium in circuit breakers can be a much better alternative for battling global warming. The prototype of a 72 kV, 20 kA (peak) supercritical CO 2 -based circuit breaker is being developed and will be tested using a synthetic test circuit. 20 kA fault current will be passed through the test breaker. The high current is generated using a capacitor bank and an inductor (resonant circuit). COMSOL simulation was used to obtain the required inductance and ensure that no flashover occurred between the turns of the inductor.